2020
DOI: 10.1177/0003319720943816
|View full text |Cite
|
Sign up to set email alerts
|

Mean Corpuscular Volume Predicts Adverse Outcomes Following Peripheral Angioplasty With Stenting and Is Associated With On-Treatment Platelet Reactivity

Abstract: Structural aspects of red blood cells have been associated with cardiovascular disease. No data linking mean corpuscular volume (MCV) to clinical outcomes and on-treatment platelet reactivity in patients with peripheral artery disease (PAD) are available. We investigated a composite of atherothrombotic events and target vessel restenosis or reocclusion following infrainguinal stenting for stable PAD. Residual platelet reactivity was measured by light transmission aggregometry (LTA) and the VerifyNow assays. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This parameter helps clinicians identify erythrocyte-related abnormalities and the type of anemia [59,60]. In the previous study, it was found that MCV, MCH, and PDW levels predicted oxidative stress in patients with STEMI [61]. In one study, patients with peripheral artery disease with low MCV levels were found to have significantly higher percutaneous intervention-related major cardiovascular events (MACE) [62].…”
Section: Discussionmentioning
confidence: 99%
“…This parameter helps clinicians identify erythrocyte-related abnormalities and the type of anemia [59,60]. In the previous study, it was found that MCV, MCH, and PDW levels predicted oxidative stress in patients with STEMI [61]. In one study, patients with peripheral artery disease with low MCV levels were found to have significantly higher percutaneous intervention-related major cardiovascular events (MACE) [62].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an association between MCV and mortality has been reported in patients presenting different diseases, such as resectable esophageal cell carcinoma, [9] chronic kidney disease, [10] liver cancer, [11] colorectal cancer, [12] and acute decompensated heart failure (ADHF). [13] In addition, MCV has been related to clinical outcomes after cardiac surgery, [14] coronary intervention, [15] chronic hemodialysis, [16] peripheral angioplasty with stenting, [17] and pancreaticoduodenectomy. [18] However, there is a lack of available information on MCV levels and clinical outcomes in ICH patients.…”
Section: Introductionmentioning
confidence: 99%